2011
DOI: 10.1007/s11738-011-0800-2
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-histological characterization of truncated leaf syndrome seedlings: an oil palm (E. guineensis Jacq.) somaclonal variant

Abstract: A comparative phenotypic and morpho-histological study was carried out on tissue culture-derived truncated leaf syndrome (TLS) and wild-type oil palm seedlings to investigate their phenotypic and morpho-histological differences. On the basis of the percentage of TLS occurence in a clone, the TLS seedlings were categorized into three groups: severe (70-100%), moderate (40-69%) and mild (\40%). Wild and TLS seedlings differ in terms of growth, vigor, leaf size and shape, root number, volume, length as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
1
1
2
Order By: Relevance
“…Rather, several plants with normal growth and development were regenerated. The above results differ from those by Habib et al (2012), who reported that large-scale somatic embryogenesis of E. guineensis was, in some cases, impaired by the regeneration of plantlets with abnormal development. However, most leaves in these plants were missing due to a partial necrosis of the leaf blades.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Rather, several plants with normal growth and development were regenerated. The above results differ from those by Habib et al (2012), who reported that large-scale somatic embryogenesis of E. guineensis was, in some cases, impaired by the regeneration of plantlets with abnormal development. However, most leaves in these plants were missing due to a partial necrosis of the leaf blades.…”
Section: Resultscontrasting
confidence: 99%
“…Moreover, the occurrence of certain morphological and anatomical anomalies in the somatic embryogenesis of the oil palm, such as the fusion of embryos, underdevelopment of apical meristems and loss of propagules´ bipolarity, has also made it difficult to establish effective methods for clonal propagation of the species's elite specimens (Habib et al 2012). Consequently, the morphological and anatomical monitoring of somatic embryogenesis of oil palm becomes crucial to better understand the process, select treatments that best minimize the occurrence of anomalies and, consequently, enhance the protocols developed (Angelo et al 2013;Silva et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Em secção transversal, pôde-se verificar a presença de estômatos apenas na face abaxial da folha, com estômatos nivelados com as demais células da epiderme e câmara subestomática ampla (Figura 1 D). No entanto, diversos autores classificam as folhas de dendezeiro como sendo anfiestomáticas e descrevem a presença de estômatos nas faces abaxial e adaxial com maior concentração na face abaxial , Habib et al, 2012. Essa diferença encontrada na presença de estômatos apenas em uma face foliar pode estar associada à maturidade do explante analisado, uma vez que, no presente trabalho foram analisadas folhas imaturas, contrariamente aos demais trabalhos que avaliaram folhas já desenvolvidas e clorofiladas.…”
Section: Estudos Morfoanatômicos Dos Estádios De Desenvolvimentounclassified
“…No entanto, próximo a essa região, também foi identificada a formação de aglomerados celulares, evidenciando a presença de calo (Figura 4 B e C)., analisando a influência de diferentes reguladores de crescimento (ANA associado com BAP) na indução de rotas embriogênicas ou organogênicas de Bactris gasipaes verificaram a presença de centros meristemáticos que, a partir do contato com esses reguladores, formaram regiões com células procambiais que deram início à rota organogênica.Através da secção longitudinal da raiz, foi verificada a presença de tecidos vasculares visíveis, a região meristemática apical da raiz onde há inicialmente um predomínio de divisões periclinais, resultando em células achatadas e enfileiradas e a região da coifa da raiz claramente distinta das demais regiões, pela presença de células com coloração mais escura (Figura 4 C). Resultados semelhantes foram encontrados porHabib et al (2012), que analisando raízes de clones de dendezeiro verificaram a presença de quatro regiões distintas na raiz: 1 = região vascular procambial, 2 = região meristemática denominada centro quiescente, 3 = região caliptrogênica ou região de células vivas da coifa e 4 = coifa.Em seção transversal das raízes formadas foi observada a presença de uma região de revestimento denominada região epidérmica, composta por células alongadas e enfileiradas contornando todo o corte da raiz. Internamente a essa camada foram verificadas de 4 a 9 camadas de células menores com formato mais arredondado que compõem a região cortical (Figura 4 D).…”
unclassified